Accelerating Kitab Reading Skills Through Dzauq and Strategic Vocabulary Acquisition - Solehudin, Muhamad (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study explores effective strategies for accelerating Kitab Kuning reading skills while fostering dzauq, an intuitive appreciation of the linguistic and spiritual beauty of classical Arabic texts. The research emphasizes the importance of vocabulary acquisition, psychological support, and innovative pedagogical approaches in overcoming challenges faced by students, such as limited vocabulary, language interference, and low confidence. Using a qualitative approach, data were collected through observations, semi-structured interviews, and document analysis involving 30 pesantren students aged 15–18 years. The findings demonstrate that structured vocabulary building, thematic nahwu and sharaf instruction, and the introduction of rhythmic recitations effectively enhance reading skills and student engagement. Moreover, cultivating dzauq helps students develop a deeper connection to the text, enabling them to overcome psychological barriers and approach Kitab Kuning as an enriching challenge rather than an overwhelming task. The research concludes that a holistic approach integrating technical mastery, emotional engagement, and vocabulary reinforcement can significantly improve Kitab Kuning learning outcomes while laying the foundation for future pedagogical innovations.